The Politics and Practice of Literacy Pedagogy: Ideology and Outcomes in Two Racially Diverse Settings. (1st October 2016) - Freedson, Margaret; Eastman, Wayne
Abstract: Discussing ideologically opposing views of beginning reading, the authors trace the politics of reading curriculum in two racially diverse New Jersey school districts working to raise the literacy achievement of traditionally underserved students through socially just literacy education .